Peningkatan Ketrampilan Membuat Minuman Jasule Untuk Imunitas Dimasa Pandemi Covid-19 Di Pangkalan Jati Cinere Depok - Tiwuk Susantiningsih; Yuni Setyaningsih; Agneta Irmarahayu; Fajriati Zulfa (Jurnal Pemberdayaan Masyarakat, 2021)
During the Covid-19 pandemic, good immunity was needed to avoid the corona virus infection. One of the efforts to prevent corona virus infection was to increase the body's immune status. High body immunity can be obtained from eating healthy foods, getting adequate rest and avoiding stress / mental stress. One local wisdom of the people in Indonesia to increasing immunity level was the habit of consuming herbal drinks which were believed to increase immunity level because there were several very useful ingredients. One of the herbal drinks made from ginger and lemon was JASULE (Jahe Susu Lemon), which was a ginger milk drink with lemon added. In this training, the participants were given material about the importance of the herbal drink JASULE (Jahe Susu Lemon). The importance of growing ginger and lemon as a medicinal plant in the yard. Also given training in making JASULE drink until all participants can make it themselves. The training activities for making herbal drinks JASULE to increase body immunity level during the Covid-19 Pandemic were held in Pangkalan Jati Cinere, Depok. This activity was well received by all participants with enthusiasm and the questions asked. Participants gained additional knowledge and skills in making herbal drinks JASULE, which can be seen from the increasing in post test scores after counseling and training in making herbal drink JASULE to increasing body immunity level during the Covid-19 Pandemic in Pangkalan Jati Cinere, Depok was 42.4% ie from 47.9% to 90.3%.